RELATIONSHIP BETWEEN POLITICS AND DAKWAH IN THE QUR'AN AND AS-SUNNAH - Badrah Uyuni; Mohammad Adnan (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2021)
This article discusses the concept of politics in Islam and its relation to dakwah. Whether politics and Islam are contradictory or whether politics itself is from Islam and needed in a series of dakwah. The method used in this study is the Method of Literature Study and analysis of scientific references related to relationship between politics and dakwah in the Qurán and the Sunnah’s perspective. There are several verses and hadiths that are displayed in this study to understand the context. The result shows that politics is a crucial thing for a Muslim, and it is wrong if someone thinks that Islam does not have to be political justice for the entire Indonesian nation.